A dialética e as letras : imagens e paradigmas do pensar no Fedro de Platão - Fabio da Silva Fortes (2019)
The debate about writing and dialectics raised in the dialogue Phaedrus, besides keeping alive a discussion of utmost importance for contemporary philosophy – the limits and possibilities of the relation between philosophy and language – is also the object of a reflection that does not show loss of vitality among Plato's scholars. After all, in the perspective of Platonic philosophy, would writing be adversary to thinking? Should we sustain, by reading the criticism that emerges in the first layer of signification of the myth of Theuth (Phdr. 274b-278b), that there is a strong contrast between two dimensions of language - the dimension of orality and writing - and, therefore, the unequivocal election of the former as the proper mode for dialectical expression? In order to contribute to this debate, by illuminating particularly the possible convergences and dissidences between the universe of letters and the dialectics in the context of Plato's work, especially within the Phaedrus, this doctoral dissertation aims at contributing, broadly speaking, to the debate on the limits and the possibilities of written language for the expression of philosophical thought. Strictly speaking, the objectives are: 1) to re-evaluate the problem of writing in Plato, based on the reflections contained especially in the Phaedrus, relating them to the plurality of subjects with which they have a relationship within the framework of the dialogue itself (rhetoric , dialectics, memory, psykhé, éros etc.); 2) in relation to the previous item, we aim at observing at what extent the reflections on the letters (γράμματα) and writing (γραφή) can be understood from the notions of image (εἴδωλον) and paradigm (παράδειγμα) and how they collaborate for the formulation of the notion of dialectic (διαλεκτική). Our hypothesis is that not only does writing appear in the Phaedrus as a consequence of the historical debate underway in Athens by the middle of the fifth century BC, on which Socrates would have presented a veiled disapproval, but also it does configure for Plato a theme of philosophical interest. We intend to show that, throughout the dialogue, while trying to answer the questions: can writing be beautiful? If so, in what conditions? There is also an answer that would go beyond a “ethics of writing” for the philosopher. Thus the own resources of the universe of writing – the letters – are also taken as elements through which the notion of dialectic associated with division (διαίρεσις) and reunion (συναγωγή) is formulated and can be understood philosophically, so that letters and writing becomes in the Platonic text not only images, but also paradigms for the determination of philosophical thinking.